Intraocular Pressure Changes after Intravitreal Bevacizumab or Ranibizumab Injection: A Retrospective Study - Mansoori, Tarannum (J Curr Ophthalmol, 2021)
PURPOSE: To determine intraocular pressure (IOP) changes after intravitreal bevacizumab or ranibizumab injection administered for various retinal disorders. METHODS: A retrospective chart review of 796 eyes of 574 patients receiving intravitreal ranibizumab (0.5 mg) and/or bevacizumab (1.25 mg) injection for different retinal diseases from March 2009 to December 2016 was performed. Ocular hypertension (OHT) was defined as IOP >21 mmHg or an increase in IOP of >5 mmHg from the baseline. IOP at the baseline and at various time periods after the injection was evaluated in the injected eyes and fellow control eyes. RESULTS: One hundred and thirty-one eyes received either a single dose of bevacizumab or ranibizumab intravitreal injection unilaterally, 222 patients received single injection in both the eyes (n = 444 eyes), and 221 eyes received multiple doses of the injection. OHT was noted in 11 eyes (1.38%), of which 3 eyes (0.38%) had transient OHT and 8 eyes (1%) had delayed and sustained OHT and among them, 3 eyes (0.4%) progressed to glaucoma. Preinjection IOP was significantly higher in the treated eyes when compared to the control untreated eyes (P = 0.006). CONCLUSIONS: Incidence of delayed and sustained OHT is low after a single or multiple intravitreal bevacizumab and ranibizumab injections. Clinicians should be aware of possibility of OHT or glaucoma after the procedure.